Analisis Evaluasi Etika Komunikasi dalam Perspesktif Studi Al-Qur’an - Nurlisana Shidqi Saili; Ali Akbar (Indo Publishing, 2025)
Effective communication plays an important role in human life, both personally and professionally. Many failures are caused by poor communication, such as a teacher's failure to transfer knowledge or a professional's failure to promote themselves. With the advancement of the digital world, communication ethics has become highly relevant, especially in addressing challenges such as the spread of hoaxes, hute speech, and cybercrime. This study uses a qualitative or literature review method. The aim of this research is to examine the application of communication ethics principles taught in the Qur'an, such as tabayyun (information clarification), qaulan sadidan (trutıful words), and gaulan ma'rufan (kind words), in the context of 21st-century digital communication, as well as the prohibitions against bad assumptions, ghibah (slander), and fitnah (spreading lies). The results of this study show that the communication ethics taught in the Qur'an are highly relevant and important to apply in 21st-century digital communication. Communication ethics principles in the Qur'an, such as qaulan sadidan (truthful words), qaulan ma' rufan (kind words), gaulan karima (noble words), qaulan ma isura (easy words), and gaulan layyina (gentle words), guide us to communicate in a polite, truthful, and respectful manner. In the digital world, these principles are highly relevant in facing challenges such as the spread of hoaxes, hate speech, and fitnah, which often occur on social media. The communication ethics in the Qur'an also emphasize the importance of tabayyun (information clarification), avoiding ghibah (slander), namimah (sowing discord), and fitnah (spreading false news). The application of these principles can help create more responsible digital communication, maintain social harmony, and prevent harm caused by false or damaging information.